Screening Current-Induced Field and Field Drift Study in HTS coils using T-A homogenous model. (June 2020) - Berrospe-Juarez, Edgar; Trillaud, Frederic; Zermeño, Víctor M R; Grilli, Francesco
Abstract: The emergence of second generation (2G) high-temperature superconductor (HTS) tapes has favored the development of HTS magnets for their applications in areas such as NMR, MRI and high field magnets. The screening current-induced field and the field drift are two major problems hindering the use of HTS tapes in the mentioned areas. Both problems are caused by the screening current, then it is necessary to have a modeling strategy capable to estimate such phenomena. Thus far, the H formulation has been a widely used approach to model medium-size systems (hundreds of tapes). However, its application to large-scale systems is still impaired by excessive computation times and memory requirements. Homogenization and multi-scaling strategies have been successfully implemented to increase the computational efficiency. In this contribution, we show that using the homogenization technique with the recently developed T-A formulation allows reducing the computation time and the amount of memory up to the point that realtime simulations of slow ramping cycles of large-scale systems are possible. At the same time, the T-A homogeneous model provides enough resolution to investigate the screening current using numerical simulations.